2018
DOI: 10.4067/s0717-95022018000301101
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the Medial Clavicular Epiphysis in the South African and Kenyan Populations

Abstract: Age estimation from clavicular ossification has been studied by many researchers based on the pattern and degree of the epiphyseal union through the use of dry bone specimens, radiographs, CT and MRI. These studies found clavicular ossification as a useful age indicator up to the third decade of life. The study aimed to document any population specific influence on age estimation using fusion processes of the clavicular epiphysis between the South African and Kenyan population groups. To achieve this objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Because of the characteristic of clavicles: low weight bearing, the longest time to maturate, easy to access, they are considered as the best candidate for accurate age estimation. The statement is correlate with Marera and Satyapal [ 9 ] study which found that estimating age from clavicle yields the most accurate result. However, methods used nowadays mainly rely on observing epiphyseal plate fusion of clavicles which could only predict age of young adult and adolescent.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Because of the characteristic of clavicles: low weight bearing, the longest time to maturate, easy to access, they are considered as the best candidate for accurate age estimation. The statement is correlate with Marera and Satyapal [ 9 ] study which found that estimating age from clavicle yields the most accurate result. However, methods used nowadays mainly rely on observing epiphyseal plate fusion of clavicles which could only predict age of young adult and adolescent.…”
Section: Introductionsupporting
confidence: 84%
“…The body is markedly affected by force and is composed with different cortical components and properties compared with acromion and sternal end. Accordingly, it is the most frequent (70%–80%) location of fracture [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the difference, however, is unclear (3,15,18). We hypothesized that these differences may be the result of differences in demographic origins and ethnicities (3,18). For that reason, this study emphasizes that reference values for one population may not be applicable to subjects from different demographic settings and ethnicities just as differences can result from using different evaluation techniques.…”
Section: Discussionmentioning
confidence: 92%
“…The reasons for the difference, however, is unclear (3,15,18). We hypothesized that these differences may be the result of differences in demographic origins and ethnicities (3,18).…”
Section: Discussionmentioning
confidence: 96%